Численное определение остаточных напряжений и деформаций в прямоугольной сварной пластине - Косенков, В. М.; Каменская, Л. А. (НТУ "ХПИ", 2008)
У роботі запропоновано спосіб числового розв’язання нестаціонарної просторової задачі термопружнопластичності. Наведено деякі результати - епюри обчислених за допомогою цього способу полів зварних напружень і деформацій.

The way of the numerical solving of the non-stationary spatial problem of thermo-elastic-plasticity is proposed. Some results is shown, they are the diagrams of fields of welding stresses and deformations, which are calculated using this method.
Keywords: сварные соединения; эпюры; сварной шов; поле напряжений; напряженно-деформированное состояние